All-Silicone-based Distributed Bragg Reflectors for Efficient Flexible Luminescent Solar Concentrators. (April 2020) - Portnoi, Mark; Macdonald, Thomas J.; Sol, Christian; Robbins, Tom S.; Li, Tao; Schläfer, Johannes; Guldin, Stefan; Parkin, Ivan P.; Papakonstantinou, Ioannis
Abstract: Luminescent Solar Concentrators (LSCs) have drawn huge interest recently as a technology to pave the way towards the seamless integration of photovoltaics to a range of high-value industries; from architecture and sports to leisure and consumer electronics. Additional device flexibility comes with the inherent ability to attain freeform shapes, expanding the possible fabrication methods, applications and retro-fitting techniques. Unfortunately, flexible LSCs suffer from curvature induced losses which can severely reduce their efficiency, inhibiting the potential of large-scale devices. In this work, we experimentally demonstrate an all-silicone based flexible LSC and Distributed Bragg Reflector (DBR) combination diminishing curvature induced losses. The DBRs, fabricated using scalable solution-based processes, exhibit optical properties precisely engineered to partner our LSCs, as well as high uniformity, resistance to temperature and curvature. Comprehensive modelling shows that for large-scale devices (1 m 2 ) we can essentially decouple the performance of the LSC from curvature, steering the technology towards commercial viability. Graphical abstract: Image 1 Highlights: We have demonstrated an all-flexible LSC and Distributed Bragg Reflector combination, allowing for efficient freeform LSCs. Both LSC and DBR consist entirely of silicone-based materials, giving homogeneity, compatibility and mechanical consistency throughout. We use a scalable, single-pot method to fabricate our DBRs and exhibit excellent control of optical properties of our multilayer structures. We show a significant reduction of the dependence of the device efficiency on curvature. We analyse the performance of large-scale LSCs using Monte-Carlo statistical models demonstrating a clear pathway to real consumer products.